Peran Brand “Kampoeng Batik Laweyan” dalam Menguatkan Batik Laweyan Untuk Meningkatkan Daya Saing Industri Batik “Kampoeng Batik Laweyan” Solo - Basworo Basworo; Sujadi Sujadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2018)
The existence of Laweyan Batik has been around since before 1500M (Mlayadipuro, 1984), with Laweyan Market and Bandar Kabanaran as a center of trade and sell of clothing material (lawe) of Pajang Kingdom which is busy and strategic at that time (Priyatmono, 2004). A visit to Laweyan proves that Laweyan is a batik area that has existed long ago, it can be seen from the form of buildings in the area (Aviarini Indrati, et al, 2011). The policy of Surakarta City Government has established Kampoeng Laweyan as a tourism area under the name of